Determinants and Impact of Digital Transformation on Small Business Performance in the Jabodetabek Area - Endika Perdana; Budi Hermana; Adi Kuswanto (Return : Study of Management, Economic and Bussines, 2024)
Small business actors are currently facing many challenges, where competition from the small business sector itself is getting tougher and facing the COVID-19 pandemic situation that hit Indonesia in early 2020, this is the biggest challenge faced by business actors, especially small businesses, small business actors may lose many consumers who transact offline. In order to survive, small business actors try new alternatives, namely by selling digitally or online. Researchers identify that the application of digital transformation can improve company performance supported by factors that influence digital transformation. The purpose of this study is to analyze the influence of the factors that support digital transformation and analyze the effect of digital transformation on company performance. This research proves that the application of digital transformation in a business or business can improve business performance for a company or organization.